THE PRINCIPLES AND POSSIBILITIES OF FORECASTING: THE PAYABLES AND RECEIVABLES BALANCE SETTLEMENTS - T. P. Karpova; V. V. Karpova (Финансы: теория и практика, 2017)
The management of the economic calculations system is within the scope of two spheres of economic knowledge - financial management and accounting. The latter has an information and analytical function preparing the basis for financial strategy development and observance of the contractual discipline in combination with an adopted accounting policy. The urgency of the issues concerning the effective management of receivables and payables is growing higher because of the continuing process of payment discipline violation and this process is very difficult to manage. Thus, the study of theoretical and practical aspects of budgeting and real-time accounting of fulfillment of obligations is considered to be very pertinent.The article highlights factors which are claimed to have a great impact on the state of payables and receivables as the most important elements of economic relations and should be taken into account while predicting the behavior of settlements with counteragents, employees and other debtors and creditors.The authors worked out the budgeting method for incurrences and repayments of indebtedness on the basis of approximated linear dependence. The method includes five stages of constructing the balance of payments: analysis and preparation of initial data for predicting receivables and payables, systematization and classification of the receivables and the payables, construction of parametric trend model for regular and irregular payables and receivables and for financial and non-financial responsibility, preparation of the aggregate forecast of movements of accounts payable and accounts receivable. Also, the authors offer the aggregate format of the balance of payments: the forecast balance of receivables and the excess of liabilities over the means of payment, on one hand, and the forecast balance of payables and the excess of the means of payment over liabilities, on the other hand. The proposed innovations will allow using free means of payment more effectively and prevent from bad debts.